Artificial light at night causes top‐down and bottom‐up trophic effects on invertebrate populations. Issue 6 (3rd August 2018) - Bennie, Jonathan; Davies, Thomas W.; Cruse, David; Inger, Richard; Gaston, Kevin J.
Abstract: Globally, many ecosystems are exposed to artificial light at night. Nighttime lighting has direct biological impacts on species at all trophic levels. However, the effects of artificial light on biotic interactions remain, for the most part, to be determined. We exposed experimental mesocosms containing combinations of grassland plants and invertebrate herbivores and predators to illumination at night over a 3‐year period to simulate conditions under different common forms of street lighting. We demonstrate both top‐down (predation‐controlled) and bottom‐up (resource‐controlled) impacts of artificial light at night in grassland communities. The impacts on invertebrate herbivore abundance were wavelength‐dependent and mediated via other trophic levels. White LED lighting decreased the abundance of a generalist herbivore mollusc by 55% in the presence of a visual predator, but not in its absence, while monochromatic amber light (with a peak wavelength similar to low‐pressure sodium lighting) decreased abundance of a specialist herbivore aphid (by 17%) by reducing the cover and flower abundance of its main food plant in the system. Artificial white light also significantly increased the food plant's foliar carbon to nitrogen ratio. We conclude that exposure to artificial light at night can trigger ecological effects spanning trophic levels, and that the nature of such impacts depends on the wavelengths emitted by the lighting technology employed. Policy implications . Our results confirm that artificial light at night, at illuminance levels similar to roadside vegetation, can have population effects mediated by both top‐down and bottom‐up effects on ecosystems. Given the increasing ubiquity of light pollution at night, these impacts may be widespread in the environment. These results underline the importance of minimizing ecosystem disruption by reducing light pollution in natural and seminatural ecosystems.